Knockdown of lncRNA MIR31HG inhibits cell proliferation in human HaCaT keratinocytes - Jintao Gao; Fangru Chen; Mingchun Hua; Junfan Guo; Yuejuan Nong; Qinyan Tang; Fengxia Zhong; Linxiu Qin (Biological Research, 2018)
Abstract Background Psoriasis is a complex, chronic inflammatory skin disease with substantial negative effects on patient quality of life. Long non-coding RNAs (lncRNAs) are able to be involved in multitudes of cellular processes in diverse human diseases. This study aimed to investigate the potential involvement of lncRNA MIR31HG in HaCaT keratinocytes proliferation. Results The study showed that MIR31HG was significantly elevated in the lesional psoriatic skin compared with normal individuals’ skin. Knockdown of MIR31HG inhibited HaCaT keratinocytes proliferation. Flow cytometry analysis showed that siRNA-mediated MIR31HG depletion induced cell cycle arrest in the G2/M phase. In addition, MIR31HG expression was found to be dependent on NF-κB activation. Conclusions NF-κB activation mediated MIR31HG upregulation plays an important role in the regulation of HaCaT keratinocytes proliferation. It could be a potential diagnostic biomarker and therapeutic target for psoriasis.